IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN PEMAHAMAN ATURAN DI LINGKUNGAN SEKITAR SISWA KELAS IV SEKOLAH DASAR - Efitriana Dwi Harvianingtyas; Rakhaprima Karima Nugraha; Susilo Tri Widodo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Pancasila Education in elementary schools requires learning processes that go beyond the mere acquisition of knowledge and instead encourage students to internalize and practice values and norms in their daily lives. In line with this need, the present study aims to describe the process of implementing the Problem Based Learning (PBL) model and the changes in students’ understanding of rules in their surrounding environment after participating in the learning activities. This study employed a descriptive qualitative approach with a case study design. The research was conducted in a fourth-grade classroom at SD Negeri Tugurejo 03, Semarang City. The implementation of PBL was supported by interactive video media presenting contextual problem situations related to rules at home, school, and the surrounding community. Data were collected through observations of learning activities, limited interviews with teachers and students, and documentation. The findings indicate that PBL promotes active learning by increasing students’ participation in questioning, discussion, and the expression of opinions, while also strengthening their understanding of rules in a more meaningful way. Furthermore, students were not only able to identify rules but also to explain their underlying reasons, consequences, and connections to rights and responsibilities within real-life contexts. These results suggest that the implementation of PBL supported by interactive video media is relevant and effective for deepening Pancasila Education learning, particularly in the topic of rules in the surrounding environment.